AKTIVITAS ANTIOKSIDASI MINYAK BUAH MERAH DARI KULTIVAR Pandanus Conoideus L YANG BERBEDA - Achmad Taher; Mery S Repasi (Jurnal Natural, 2009)
The research was aimed to test the antioxidative activity of the buah merah oil from two cultivars Pandanus conoideus L; MTW-W and MMS-M. In vitro analysis the antioxidative activity of the buah merah oil was determinated using Thiobarbituric Acid test (TBA test). The research revealed that the buah merah oil from MTW-W cultivar produces highest antioxidative activity than MMS-M cultivar. The antioxidative activities of these two tested cultivars are 24 – 70% and 30 – 53%, respectively.